Impact of the comprehensive outpatient rehabilitation on reducing intensification of depressive symptoms in people over 60 years of age - Czarkowska , Magdalena; Saran, Tomasz; Mazur, Anna; Horoch, Andrzej; Panasiuk , Lech (Polish Journal of Public Health, 2019)
Introduction. As a result of involution processes and diseases, changes occur in the human body, as a result of which, psychophysical fitness declines with age. Comprehensive rehabilitation is the way of improving and maintaining health condition, including, among others, the appropriate level of physical activity and the quality of affective functioning. This type of program was carried out as part of the Outpatient Healthcare Home (DDOM) at the Witold Chodźko Institute of Rural Health in Lublin. Aim. The objective of the present study was to assess the impact of comprehensive ambulatory rehabilitation, including tailored endurance training preceded by an ergospirometry test, on indicators demonstrating the level of involvement in daily physical activities and the severity of depressive symptoms of patients over 60 years of age receiving health services at DDOM. Material and methods. The study involved 60 seniors participating in the rehabilitation cycle implemented as part of the services provided to patients at DDOM of the Witold Chodźko Institute of Rural Health in Lublin. The tests were carried out in the test-retest model on the first and last day of the kinesiotherapy cycle. The tests were performed with use of International Physical Activity Questionnaire IPAQ and Geriatric Depression Scale GDS. The patient rehabilitation program included adapted systemic kinesiotherapy (endurance training with a load determined according to individual exercise capacity, as determined on the basis of the ergospirometry test) and local kinesiotherapy and physical therapy adapted to the needs resulting from the condition of the musculoskeletal system. Results. After the completion of the rehabilitation cycle we compared the tests carried out before it, and the patients received higher scores in the scales of IPAQ questionnaire for measuring weekly, intensive and mode-rate physical activity and time required for walking and were less likely to spend their time sitting or lying down. There were also lower scores of the respondents in GDS scale used to assess the severity of depressive symptoms. Conclusions. As a result of the rehabilitation program applied, DDOM patients simultaneously obtained the desired changes in the level of involvement in physical activity and minimization of the intensity of depressive symptoms.